2023
DOI: 10.1108/ajems-08-2022-0315
|View full text |Cite
|
Sign up to set email alerts
|

Investigating predictors of medical students' intentions to engagement in volunteering during the health crisis

Abstract: PurposeThe purpose of the present paper is to investigate Algerian medical students' intention to participate in volunteer work during the coronavirus disease 2019 (COVID-19) pandemic.Design/methodology/approachThe authors adopted an extended theory of planned behavior (TPB) framework by integrating the constructs of personal moral norms and perceived risk of COVID-19 and followed a self-administered questionnaire survey to collect data among a convenience sample of medical students (n = 267) in five Algerian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 63 publications
(225 reference statements)
0
19
0
Order By: Relevance
“…(2011). Perceived risk of COVID-19 infection was measured with the scale drawn from Mouloudj and Bouarar (2023) and Sánchez-Cañizares et al. (2021).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…(2011). Perceived risk of COVID-19 infection was measured with the scale drawn from Mouloudj and Bouarar (2023) and Sánchez-Cañizares et al. (2021).…”
Section: Methodsmentioning
confidence: 99%
“…The second change involves adding two constructs, level of self-efficacy and perceived risk of COVID-19 infection, into the original TAM. As a consensus, some studies have proven that self-efficacy was positively related to volunteering intention (Grano et al, 2008;Laguna et al, 2017), and other studies have shown that the perceived risk of COVID-19 contributed to reducing the intent to volunteer in the context of the COVID-19 crisis (Lazarus et al, 2021;Maietti et al, 2021;Mouloudj and Bouarar, 2023).…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
See 3 more Smart Citations